Factors associated with social support for family members who care for stroke survivors - Anna Kavga; Ioannis Kalemikerakis; Theocharis Konstantinidis; Ioanna Tsatsou; Petros Galanis; Eugenia Karathanasi; Ourania Govina (AIMS Public Health, 2022)
Introduction: Vascular strokes are a primary cause of long-term disability for adults, with many social consequences for the patient, the family and healthcare systems worldwide.